Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1039/c6py00048g
|View full text |Cite
|
Sign up to set email alerts
|

Amidation of triglycerides by amino alcohols and their impact on plant oil-derived polymers

Abstract: Amidation of plant oils with amino alcohols was methodologically examined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 56 publications
(62 reference statements)
0
45
0
Order By: Relevance
“…Industrially, fatty amides are currently produced by using a two‐step process (Scheme ): the conversion of triglycerides into fatty acid esters, followed by a high‐temperature aminolysis to produce fatty amides . Several studies have reported the direct amidation of triglycerides with amino alcohols or isopropylamine by using basic promoters such as methoxides, NaOH/CaO, Na‐doped Ca(OH) 2 , and Li‐doped CaO, or by using solid acid catalysts or biocatalysts . However, reports on the direct amidation of triglycerides with NH 3 remain scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Industrially, fatty amides are currently produced by using a two‐step process (Scheme ): the conversion of triglycerides into fatty acid esters, followed by a high‐temperature aminolysis to produce fatty amides . Several studies have reported the direct amidation of triglycerides with amino alcohols or isopropylamine by using basic promoters such as methoxides, NaOH/CaO, Na‐doped Ca(OH) 2 , and Li‐doped CaO, or by using solid acid catalysts or biocatalysts . However, reports on the direct amidation of triglycerides with NH 3 remain scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the appearance of a peak at 2.05 ppm can be ascribed to −CH 2 − protons in the α position of the CO of an amide group, according to the literature . As can be seen in Scheme , the trans ‐amidification yield decreases the content of functionalized triglycerides and increases the formation of free aliphatic chains, resulting in a decrease in the final cross‐linking ratio.…”
Section: Resultsmentioning
confidence: 71%
“…[36][37][38] As can be seen in Scheme 1, the trans-amidification yield decreases the content of functionalized triglycerides and increases the formation of free aliphatic chains, resulting in a decrease in the final cross-linking ratio. [36][37][38] As can be seen in Scheme 1, the trans-amidification yield decreases the content of functionalized triglycerides and increases the formation of free aliphatic chains, resulting in a decrease in the final cross-linking ratio.…”
Section: H Nmr Monitoring Of Reactionmentioning
confidence: 99%
“…The synthesized methacrylate monomers based on high oleic soybean oil, depending on the nature of the branches in the side chain, have a wide range of glass transition temperatures [ 16 ]. In further studies, Tang and co-authors used more than twenty amino alcohols to establish the mechanism of amidation of plant oils, in particular high-oleic soybean oil [ 8 ]. Depending on the nature of the acyl fatty acid and amide structures, the polymers have a wide range of glass transition temperatures – from viscoelastic to thermoplastic materials.…”
Section: Features Of Synthesis Of Vinyl Monomers From Plant Oilsmentioning
confidence: 99%
“…The total production of plant oils in the world in 2019 amounted to more than 200 million tons, of which about 15% are used as raw materials for the synthesis of new chemical compounds and materials [ 6 ]. The presence of plant oils or their derivatives (fatty acids) in various compositions of polymeric materials improves their optical (gloss), physical (flexibility, adhesion) [ 7 , 8 ], and chemical (resistance to water and chemicals) properties [ 9 ]. The synthesis of biobased monomers from renewable resources is a promising platform for the synthesis and implementation of new environmentally friendly industrial polymer materials [ 10 ].…”
Section: Introductionmentioning
confidence: 99%